2016
DOI: 10.1200/jco.2016.68.2278
|View full text |Cite
|
Sign up to set email alerts
|

Psychoeducational Intervention to Reduce Fear of Cancer Recurrence in People at High Risk of Developing Another Primary Melanoma: Results of a Randomized Controlled Trial

Abstract: Purpose People with a history of melanoma commonly report a fear of cancer recurrence (FCR), yet psychologic support is not routinely offered as part of ongoing melanoma care. This randomized controlled trial examined the efficacy of a psychoeducational intervention to reduce FCR and improve psychologic adjustment in this patient group compared with usual care. Methods The intervention comprised a newly developed psychoeducational resource and three telephone-based psychotherapeutic sessions over a 1-month per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
122
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(123 citation statements)
references
References 44 publications
1
122
0
Order By: Relevance
“…After removal of duplicates, 5738 titles and abstracts were screened, and 406 full‐text articles were reviewed. From this, we included 41 studies (n = 6038 participants) . The selection of articles, including reasons for exclusion, is outlined in Data S4.…”
Section: Resultsmentioning
confidence: 99%
“…After removal of duplicates, 5738 titles and abstracts were screened, and 406 full‐text articles were reviewed. From this, we included 41 studies (n = 6038 participants) . The selection of articles, including reasons for exclusion, is outlined in Data S4.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous research we firstly developed and piloted a psychoeducational resource, delivered in booklet format, which was judged positively by patients and healthcare providers in terms of the quality and quantity of information, its value and capacity to address unmet needs. We then piloted and evaluated in a randomized controlled trial the 1‐month and 6‐month efficacy of a new psychological intervention to reduce FCR and improve psychological adjustment and found the intervention to be effective . We now report, for the first time, the longer‐term effects of this brief, tailored psychological intervention for people with a history of early‐stage melanoma.…”
mentioning
confidence: 97%
“…As a consequence, many people who have had melanoma often experience fear of cancer recurrence (FCR) or progression. Recent studies have shown that over 70% of people with a history of melanoma report levels of fear of melanoma recurrence indicative of a need for clinical intervention; a proportion higher than those documented for other cancers …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Common reactions include excessive worry and rumination, difficulty concentrating, insomnia, increased use of alcohol and other drugs, social withdrawal and somatic complaints (Kasparian, 2013). There is strong evidence that psychological intervention can improve psychological outcomes (Boesen et al, 2005;Dieng et al, 2016).…”
Section: Essential Requirementsmentioning
confidence: 99%